2003
DOI: 10.1006/dbio.2002.0865
|View full text |Cite
|
Sign up to set email alerts
|

The Step-Wise Assembly of a Functional Nucleolus in Preimplantation Mouse Embryos Involves the Cajal (Coiled) Body

Abstract: After fertilization, ribosomal RNA synthesis is silenced during a period which depends on the species. Data concerning the reassembly of a functional nucleolus remain scarce. We have examined by immunocytochemistry, Western blots, and BrUTP microinjection the dynamics of major nucleolar proteins during the first cycles of mouse embryogenesis, in relation to rDNA transcription sites and coilin, a marker of Cajal bodies. We show that: (1) the reinitiation of rDNA transcription occurs at the two-cell stage, 44-45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 81 publications
(89 reference statements)
6
80
2
3
Order By: Relevance
“…The developmental arrest just prior to the blastocyst stage may reflect the maternal-to-zygotic transition in the translation machinery and the increased need for protein synthesis during blastocyst formation. The resumption of rRNA transcription is first detected at the two-cell stage in parallel with the major transcriptional activation of the zygotic genome, and rRNA synthesis gradually increases thereafter (12,21,71). The rate of ribosomal protein synthesis (31), along with the number of ribosomes (47), rises sharply after the eight-cell stage, followed by increased rates of protein synthesis at the blastocyst stage (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developmental arrest just prior to the blastocyst stage may reflect the maternal-to-zygotic transition in the translation machinery and the increased need for protein synthesis during blastocyst formation. The resumption of rRNA transcription is first detected at the two-cell stage in parallel with the major transcriptional activation of the zygotic genome, and rRNA synthesis gradually increases thereafter (12,21,71). The rate of ribosomal protein synthesis (31), along with the number of ribosomes (47), rises sharply after the eight-cell stage, followed by increased rates of protein synthesis at the blastocyst stage (10).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive reticulation of the NPB periphery takes place in the four-to eight-cell stage, while the fibrillar sphere remains in the core of the nucleolus until the morula stage (21). Active transcription was detected in the peripheral regions preceded by the assembly of the nucleolar components therein (7,13,71), whereas the fibrillar spheres take no part in transcription (30).…”
mentioning
confidence: 99%
“…After fertilization, the maternally derived, transcriptionally inactive nucleolus appears in both male and female pronuclei and in the embryonic nuclei until the four-cell or eightcell stage; that is, it is present until EGA (Zatsepina, Baly, Chebrout, & Debey, 2003). Although the nucleolus at this stage appears to be inactive and shows a highly compacted structure, studies with mice have revealed that it is essential for early embryonic development (Ogushi et al, 2008;Ogushi & Saitou, 2010).…”
Section: Nucleolimentioning
confidence: 99%
“…This functionally related organization is disassembled, when the rDNA is silenced during mitosis and during centre period of meiosis, when the rRNA synthetic and rRNA processing machineries become separated (Svarcova et al 2008). This event occurs at the end of telophase in somatic cells (Dousent et al 2000) and at the EGA in early embryos (Hyttel et al 2000;Kovalská et al 2010;Laurincik et al 2003;Verheggen et al 2000;Zatsepina et al 2003). At least in somatic cells, the re-assembly of the nucleolus occurs as a well-organized sequential process that is well described (Svarcova et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…This process includes the minor activation of the embryonic genome (which probably begins in the zygote) followed by a major activation at a later species-specific stage of development (Memili & First 1999;Hernandez-Verdun et al 2002;Kovalská et al 2010;Maddox-Hyttel et al 2005;Svarcova et al 2007aSvarcova et al , b, 2008. The EGA involves the activation of ribosomal RNA (rRNA) genes (rDNA), that are transcribed by RNA polymerase I (RNA pol I; Hyttel et al 2000;Maddox-Hyttel et al 2005;Laurincik et al 2000;Viuff et al 2002;Zatsepina et al 2003), new messenger RNA (mRNA) production (RNA polymerase II-RNA pol II) and formation of transfer RNA (tRNA) and 5 S rRNA (RNA polymerase III-RNA pol III; Kovalská et al 2010).…”
Section: Introductionmentioning
confidence: 99%